Melampaui Sekularisasi : Meninjau Ulang Peran Agama di Ruang Publik pada Era Disrupsi - Wahyuni, Dwi (Hanifiya: Jurnal Studi Agama-Agama, 2021)
Is the theory of secularization dead? It seems not. The idea of secularization continues to develop and shows that secularization will never occur totally, but it will not be buried into a failed theory. However, since the world today is already in a reality far different from the era of the emerging secularization theory, secularization must be transcended. Nowadays, the world has entered a period of disruption marked by technological progress due to the Industrial Revolution 4.0. In this era, there have been significant changes in religious life. This article aims to complement the literature review regarding how religion should play a role in the public sphere in the era of disruption so that the benefits of religion can be felt in real life. Data collection was carried out using literature study techniques. Data analysis was carried out using the Miles and Huberman model. The results of this study indicate that religion does not have to be isolated from the public sphere, so far as the public sphere can be a common space to express the various religions that exist and religion is not only understood as symbolic, but is deeper in understanding the authenticity of religion. One important thing to avoid is the domination of one faith or one religious understanding within religion. The dynamics and dialectics of the various religious identities that exist can become cultural assets to build a better public life. Failure to neutralize the domination of one religion or religious understanding in religion in the public sphere will bring the world back to a dark past, full of wars and violence.